Thermal Marangoni trapping driven by laser absorption in evaporating droplets for particle deposition. Issue 41 (13th October 2022) - Goy, N.-A.; Bruni, N.; Girot, A.; Delville, J.-P.; Delabre, U.
Abstract : Laser absorption triggers Marangoni flows to concentrate particles and control particles' deposition in evaporating droplets. Abstract : Controlling the deposition of particles is of great importance in many applications. In this work, we study particle deposition driven by Marangoni flows, triggered by laser absorption inside an evaporating droplet. When the laser is turned on, thermal gradients are generated and produce a toroidal Marangoni flow that concentrates the particles around the laser beam and ultimately controls the final deposition. We experimentally characterize the radius of the Marangoni flows as a function of the laser parameters. Counter-intuitively, the radius of the Marangoni region appears to remain constant and is not proportional to the thickness of the drop which decreases due to evaporation. We develop a model to predict the size of the Marangoni region that combines evaporative flows and laser-induced Marangoni flows. The experimental data are in good agreement with the predictions, allowing us to estimate the particle overconcentration factor resulting from the laser heating effects. The addition of surfactants to the solution allows the coupling of solutal Marangoni flows with thermal ones to achieve a final micron-scale deposit located at the laser spot. These results pave the way for new methods with high tunability provided by spatio-temporal light control for surface patterning applications.